Parameters Optimization Development on Relative Density and Compression Strength of AlSi10Mg Sample Produced by Selective Laser Melting using Response Surface Method. - S Wahab, M; A Raus, A; Ibrahim, M; Kamarudin, K.; Aqeel, Ahmed; Z Radzi, E; M Amir, I (International Journal of Engineering and Technology, 2019)
This paper investigates the effect of main process parameters such as laser power, scanning speed and hatching distance of selective laser melting process via relative density and compression strength using response surface method. Central composite design with three factor and three level has been used to develop the mathematical models on the relative density and compression strength of AlSi10Mg samples. The maximum and minimum relative density value recorded from the experiment measurement were 99.4785% and 97.2807% which occurred at design level 16 and 2. Meanwhile the maximum and minimum value of compression strength recorded were 545.578 MPa and 456.432 MPa which occurred at design level 15 and 2. The adequacy of the suggested mathematical models were verified from the analysis of variance (ANOVA) method and used to determine the optimized results. The optimized results on relative density and compression strength from Design Expert software were 99.3547 % and 545.578MPa, respectively occurred at 348.14 watt of laser power, 1483.25 mm/s scan speed and 0.1207 mm hatch distance. The optimized parameters were confirmed with three fabricated samples with an average value of 98.1123 % relative density and 540.597 MPa. These values were within 95% confidence level and evidenced that the developed models were adequate for both experiments.Â Â